Asset pricing in developed and emerging markets:a survey - Mohamad, Azhar; Hakim, Shabir Ahmad (Penerbit UTM Press, 2016)
Asset pricing theory states that investors should be rewarded for the risks that are associated with the state variables, in addition to market risks, which affect their investment opportunity sets. The state variables, however, are latent variables that vary (a) within developed markets (which consist of segmented and international markets); (b) between developed and emerging markets. In this paper, we provide an evaluation of the development of asset pricing theory and an identification of factors that are pervasive and priced in both developed and emerging markets. This survey of the literature suggests there is a need for distinctive asset pricing models that consider the unique characteristics of both markets.